KAJIAN LOKUSI, ILOKUSI, DAN PERLOKUSI DALAM WACANA KELAS AKSELERASI SMPN I KOTA BENGKULU - Sari, Novia (UNIB Press, 2015)
This thesis due to describe the speech act of locution, Ilocution, and perlocution text in opening, explaning, and closing the lesson in VIII th acceleration class in SMPN I Kota Bengkulu. The method that use in this thesis is qualitative descriptive. In collecting the data the writer used these steps: a) transcription, b) coding, c) identification and classification, d) analyzing the data, e) conclution. From the analized and descation can be conclude that teacher and students when did the classroom interaction in opening, explaining, and closing, used locution act such as question, informing, instruction stating, greeting, perfoming, agreement, giving turn, asking, giving opinion, suggestion, remining, explaining, reading, exclamatory, instructing, informing, agreement, and greeting. Ilocution act such as question, informing, instruction, stating, greeting, performing, agreement, giving turn, asking, and saying thanks. Speech act that usually used were questioning instructing, informing, agreement and greeting. Ilocution that used by the teacher and student. In opening the lesson, explaining and closing the lesson, direct act, accretive, expressive and comissive. The act that dominant are direct act. The direct act that common found in this term were questioning, imperative that used question words. For exampale “Kalau begitu apa sih Sirkum Pasifik dan Sirkum Mediterania?”. Imperactive direct speech act signed by imperative verb. Than add by verb kan and verb lah. Example of direct imperative ““Silakan…”. The expression that used were greeting and saying thank by using linguistics character, “Terima kasih, Bu”. Acertive act that found were statement and explanation. In a while tie comissive promising act. In linguistics act promising something such as “Buku paket akan diantar nanti…” Perlocution act in opening that lesson, explaining the lesson, as act that responanble and undestanable, responable and un undestenable also speech act that undestanable by the teacher or the student.